A robust and facile label-free method for highly sensitive colorimetric detection of ascorbic acid in fresh fruits based on peroxidase-like activity of modified FeCo-LDH@WO3 nanocomposite - Dadakhani, Sonya; Dehghan, Gholamreza; Khataee, Alireza (Pergamon-Elsevier Science Ltd, 2023)
Many compounds such as amino acids and oligonucleotides have been shown to effectively change peroxidase-like activity of nanoparticles. While a few studies have focused on mimicking the active site of natural enzymes on nanozymes and thus increasing their substrate affinity. Therefore, in this work, the surface of FeCo@WO3 nanocomposite was modified using guanosine triphosphate (GTP) to mimic the histidine of peroxidase enzyme's active site and its modification was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Fourier-transform infrared spectroscopy (FT-IR). Then, the peroxidase-mimicking activity of the modified nanocomposite was tested using a colorimetric method, based on the oxidation of 3,3 & PRIME;,5,5 & PRIME;-tetramethylbenzidine (TMB) in the presence of hydrogen peroxide (H2O2). It was found that GTP improves the activity of FeCo@WO3 as a natural peroxidase active site's distal histidine residue. Ascorbic acid (AA) is a powerful antioxidant that induces the reduction of blue color (oxidized TMB) ox-TMB to colorless TMB. The colorimetric method was applied for the sensitive detection of AA in common fruits. The linear range of AA was 10-100 & mu;M with a limit of detection (LOD) of 0.27 & mu;M, which provides a rapid and sensitive method for testing AA in the field of food analysis.
Keywords: Nanozyme; Biosensor; Guanosine triphosphate; Peroxidase-mimicking nanocomposite; Ascorbic acid